2012
DOI: 10.1182/blood-2011-09-377648
|View full text |Cite
|
Sign up to set email alerts
|

Platelet TGF-β1 contributions to plasma TGF-β1, cardiac fibrosis, and systolic dysfunction in a mouse model of pressure overload

Abstract: Circulating platelets contain high concentrations of TGF-␤1 in their ␣-granules and release it on platelet adhesion/activation. We hypothesized that uncontrolled in vitro release of platelet TGF-␤1 may confound measurement of plasma TGF-␤1 in mice and that in vivo release and activation may contribute to cardiac pathology in response to constriction of the transverse aorta, which produces both high shear and cardiac pressure overload. Plasma TGF-␤1 levels in blood collected from C57Bl/6 mice by the standard re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
173
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 168 publications
(191 citation statements)
references
References 51 publications
(48 reference statements)
13
173
1
2
Order By: Relevance
“…Ongoing microvascular damage, even in younger patients without complications, may lead to increased platelet turnover, degranulation, and subsequent TGF-β1 release into circulation as recently described in a mouse model of cardiac pressure overload. 35 Interestingly, we found that CRP was not significantly elevated in MFS, suggesting a different biomarker profile from VEDS.…”
Section: 13mentioning
confidence: 72%
“…Ongoing microvascular damage, even in younger patients without complications, may lead to increased platelet turnover, degranulation, and subsequent TGF-β1 release into circulation as recently described in a mouse model of cardiac pressure overload. 35 Interestingly, we found that CRP was not significantly elevated in MFS, suggesting a different biomarker profile from VEDS.…”
Section: 13mentioning
confidence: 72%
“…The contributions of other cell types have not been convincingly documented. Platelets have been suggested to be an important source of TGF-β1 in the pressureoverloaded myocardium (29); however, their role as a source of growth factors in the infarcted myocardium has not been systematically investigated. Lymphocyte subsets and mast cells infiltrate the infarcted heart (30)(31)(32)(33) and are capable of producing TGF-βs.…”
Section: Regulation Of Tgf-β Isoforms In Myocardial Infarctionmentioning
confidence: 99%
“…Platelets contain 40-to 100-fold more TGF-␤1 than other cell types (2,3), perhaps reflecting a role in wound healing after hemostasis is achieved. The pathological importance of platelet TGF-␤1 has been highlighted by the recent discovery that platelet TGF-␤1 can confer metastatic potential on tumor cells in synergy with NFB signaling (4), and our recent report that targeted deletion of platelet and megakaryocyte TGF-␤1 can protect mice from developing cardiac hypertrophy, fibrosis, and systolic dysfunction in response to constriction of the transverse aorta (5).…”
mentioning
confidence: 99%